The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1029/94jb02159
|View full text |Cite
|
Sign up to set email alerts
|

The origin of Kenya rift plateau‐type flood phonolites: Evidence from geochemical studies for fusion of lower crust modified by alkali basaltic magmatism

Abstract: Geochemical investigations support the petrogenesis of Kenya rift plateau‐type flood phonolites (14–11 Ma) by partial melting of an alkali basaltic material at lower crustal pressures. High‐pressure/high‐temperature experiments on a natural plateau phonolite (Hay and Wendlandt, this issue) document multiple saturation of augite, andesine, titanomagnetite, and phlogopite at 0.7 GPa, 1000°C, XCO2 = 0.42, with amphibole appearing at 975°C. A least squares solution to major element modeling, involving subtraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 34 publications
1
4
0
1
Order By: Relevance
“…Seismic tomography reveals a high-velocity lower crust (V p = 7.1-7.8 km/s) in the Panxi area [48] , which has been attributed to the underplating of plume-derived basaltic melts in the crust-mantle boundary [9] . The pressure condition and basaltic composition of the lower crust in the Panxi area are very similar to those of partial melting model put forward by Hay et al [46,47] . On the other hand, positive Sr anomaly of the Maomaogou intrusion implies that its source may contain plagioclase-rich cumulates.…”
Section: Petrogenetic Evaluationsupporting
confidence: 57%
See 1 more Smart Citation
“…Seismic tomography reveals a high-velocity lower crust (V p = 7.1-7.8 km/s) in the Panxi area [48] , which has been attributed to the underplating of plume-derived basaltic melts in the crust-mantle boundary [9] . The pressure condition and basaltic composition of the lower crust in the Panxi area are very similar to those of partial melting model put forward by Hay et al [46,47] . On the other hand, positive Sr anomaly of the Maomaogou intrusion implies that its source may contain plagioclase-rich cumulates.…”
Section: Petrogenetic Evaluationsupporting
confidence: 57%
“…On the basis of experiments and geochemical elucidation, Hay et al [46,47] proposed that Kenya rift plateau-type flood phonolites were generated by partial melting of alkali basaltic material under lower-crustal pressures. Seismic tomography reveals a high-velocity lower crust (V p = 7.1-7.8 km/s) in the Panxi area [48] , which has been attributed to the underplating of plume-derived basaltic melts in the crust-mantle boundary [9] .…”
Section: Petrogenetic Evaluationmentioning
confidence: 99%
“…There is a predominantly alkali basaltic source with contributions from a lower crustal protolith (Hay et al, 1995). According to Macdonald (1994), all major sequences show evidence of extensive polybaric fractionation within the upper mantle and lower crust.…”
Section: Distribution and Types Of Volcanismmentioning
confidence: 98%
“…Some of the most recent geophysical work from the Kenya Rift can be found in Prodehl et al (1994a) and Fuchs et al (1997). Geological, geochemical and petrological perspectives are discussed by Latin et al, (1993), Macdonald et al, (1994), Hay et al, (1995a), Hay et al, (1995b), Wendlandt et al, (1995). Only some of the most important results will be briefly outlined here.…”
Section: Previous Geophysical Investigationmentioning
confidence: 99%
“…To explain the estimated basaltic magma (924,000 km3) generated beneath the rift zone in the past 30 Ma Latin et al, (1993) infer that the asthenospheric mantle must continually upwell through the melting region (extending from 70 to 150 km in depth) with a vertical velocity of between 40 and 140 mm/yr. Further geochemical studies (high-pressure / high-temperature experiments on phonolites; Hay et al, 1995a) suggested that alkali basaltic magmas may have injected and/or underplated the lower crust in central Kenya prior to the rift-related basaltic volcanism at the surface, between 23-14 Ma. Hay et al (1995b) integrated geophysical data (seismic refraction and gravity) and petrological results to model an extensive lens of anomalously high density / high velocity material in the lower crust beneath the rift axis representing material of basaltic composition; the model supports the idea that the subrift crust was extensively modified by underplating and/or basaltic intrusion and subsequent partial melting.…”
Section: 27mentioning
confidence: 99%